1992
DOI: 10.1007/bf00402550
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of linoleic-acid-enriched diet on albuminuria and lipid levels in Type 1 (insulin-dependent) diabetic patients with elevated urinary albumin excretion

Abstract: Summary. We conducted a 2-year prospective randomised study to investigate the effects of a linoleic-acid-enriched diet on albuminuria and lipid levels in Type 1 (insulin-dependent) diabetic patients with elevated urinary albumin excretion (overnight urinary albumin excretion rate between 10 and 200 gg/min). Thirty-eight patients were randomly assigned to increase dietary polyunsaturated:saturated fatty acids ratio to 1.0 by replacement of saturated fat with linoleicacid-rich products (n = 18, two dropouts, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…Recently, Dullart et al (45) observed that a linoleic-acid-enriched diet prevented the decrease in GFR over a 2-year follow-up period in IDDM patients with elevated UAE patients, which suggests that this kind of diet can alter renal hemodynamics. The increased P/S ratios in the LPD and the test diet do not seem to be related to the observed decrease in GFR, because the reduction in GFR was of a similar magnitude, despite a difference in the P/S ratio in the the two diets.…”
Section: Effect Of Ud Lpd and The Test Diet On Hyperfiltering And Nmentioning
confidence: 97%
“…Recently, Dullart et al (45) observed that a linoleic-acid-enriched diet prevented the decrease in GFR over a 2-year follow-up period in IDDM patients with elevated UAE patients, which suggests that this kind of diet can alter renal hemodynamics. The increased P/S ratios in the LPD and the test diet do not seem to be related to the observed decrease in GFR, because the reduction in GFR was of a similar magnitude, despite a difference in the P/S ratio in the the two diets.…”
Section: Effect Of Ud Lpd and The Test Diet On Hyperfiltering And Nmentioning
confidence: 97%
“…8 Of 48 included randomised controlled trials in the other review, 24 were included in the current review. Of the remaining 24 randomised controlled trials, 10 did not compare reduced fat intake with usual fat intake (they were included as they modified fat), [53][54][55][56][57][58][59][60][61][62][63] and 13 aimed to reduce weight in some or all participants so were ineligible for the current review. [64][65][66][67][68][69][70][71][72][73][74][75][76] Only one trial was eligible for this review but was not included as no data were provided on body weight, body mass index, or waist circumference.…”
Section: Effects Of Reduced Fat Intake On Body Weightmentioning
confidence: 99%
“…Diet composition was estimated with a computer-assisted nutrient database (17). In the dietary intervention trial, butter and saturated margarines were replaced by polyunsaturated margarines, and saturated fat from meat and dairy products was restricted (15). Cholesterol was reduced, but total fat intake was unchanged.…”
mentioning
confidence: 96%
“…In addition, we evaluated whether this polymorphism is a determinant of the lipoprotein response to a linoleic acid-enriched, low-cholesterol diet in type 1 diabetes. viously participated in a diet study and were randomized to increase their dietary polyunsaturated:saturated fatty acids ratio to 1.0 by replacement of saturated fat with linoleic acid (15). Venous blood was obtained after a 10-h fast.…”
mentioning
confidence: 99%